Evaluation of Food for Work Programs (August-October, 1979) Final Report - Planning Commission (Planning Commission, 1980)
It is the general experience in India that the benefits of most of the welfare schemes and development programmes had accrued to the better off sections of the society. This has happened despite the fact that eradication of poverty and unemployment has been one of the main goals of our developmental efforts since independence. The poor strata, particularly in the rural areas, have remained deprived of its due share.
Programme Evaluation Organisation, Planning Commission, Government of India